Prying open fortress Europe : the turn to sectoral labor migration - Caviedes, Alexander A., 1969- (Lexington Books, 2010)
"Prying Open Fortress Europe: The Turn to Sectoral Labor Migration is unique in the field of migration studies because it traces the microeconomic motivations of the relevant economic actors who influence labor migration policy. This book updates the study ofthe political economy of immigration through a focus on the central and proactive role of employers, exploring how they interact with trade unions and government to reconfigure the labor migration paradigm in Western Europe. By doing so, this book is attentive to the logic behind their strategies, being sensitive to macroeconomic changes that produce sectorally variant policy outcomes. Beyond offering a microeconomically informed explanation for immigration policy, the study transcends the field of migration studies by offering insights relevant to larger debates concerning the nature of national varieties of capitalism. Challenging the "national models" understanding of capitalism through a multicountry, multisectoral study of employers' policy preferences, it demonstrates how in the area of labor migration, economic branches evidence different worker flexibility needs that lead to differing policy results within countries yet similar responses in the same industries of different countries." "Although this book's case studies examine policy development and the role of German, British, Austrian, and Dutch employers, the central comparison is between Germany, with its highly regulated economy, and the more laissez-faire United Kingdom. It analyzes labor migration policy with four concentrations - IT, hospitality, construction, and metalwork - in order to illustrate the impact of differing worker flexibility requirements upon employer calculations."--Jacket